2021
DOI: 10.3390/en14227571
|View full text |Cite
|
Sign up to set email alerts
|

Review on the Importance of Gender Perspective in Household Energy-Saving Behavior and Energy Transition for Sustainability

Abstract: Energy-saving and efficiency represent a crucial role in achieving a clean environment as well as economic and social development, providing substantial benefits to stakeholders, including householders. Better cost savings can be achieved by simply changing behavior. However, real energy users lack proper technical energy knowledge, awareness, and education in most cases. In most countries, women are involved in a higher percentage of energy activities in household chores but have less gender participation in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 69 publications
0
18
0
Order By: Relevance
“…Gender accounts for crucial roles from a social aspect and energysaving process analysis because men and women have different needs. Existing gender norms, including the power relations between them, are likely to focus less on the benefits of women in most countries where socially and culturally defined gender norms have created barriers to energy-related activities (Shrestha et al, 2021). The predefined norms that are not in favor of women engaging in energyrelated activities that would improve women's welfare exacerbate poverty among women (ENERGIA, 2019).…”
Section: Review Of Literature On Gender Role DI Erentiationmentioning
confidence: 99%
See 3 more Smart Citations
“…Gender accounts for crucial roles from a social aspect and energysaving process analysis because men and women have different needs. Existing gender norms, including the power relations between them, are likely to focus less on the benefits of women in most countries where socially and culturally defined gender norms have created barriers to energy-related activities (Shrestha et al, 2021). The predefined norms that are not in favor of women engaging in energyrelated activities that would improve women's welfare exacerbate poverty among women (ENERGIA, 2019).…”
Section: Review Of Literature On Gender Role DI Erentiationmentioning
confidence: 99%
“…Remarkably, in their study "Review on the importance gender perspective in household energy saving and energy transition for sustainability, " Shrestha et al (2021) concluded that reviewing household energy-saving behavior while keeping gender roles in consideration led to gender-sensitive energy policies that had a remarkable role in changing people's mindset and perceptions to increase motivation, gender participation, and change habits. Ultimately, gender energy-saving behavior has the strength to achieve SDG goal 7, in terms of energy security, accessibility, and affordability for all, thus having a positive impact and reducing energy poverty.…”
Section: Review Of Literature On Gender Role DI Erentiationmentioning
confidence: 99%
See 2 more Smart Citations
“…The review presented by Shrestha et al [12] on household energy-saving behaviour highlighted the importance of gender roles in energy-saving and management in households. The study further showed that occupant-specific variables such as gender, income, family composition, education, headship, age-group, habits, and other socio-economic factors significantly influence energy-saving behaviours.…”
Section: Introductionmentioning
confidence: 99%